Search for a heavy neutral particle decaying to eμ, eτ, or μτ in pp collisions at √s =8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
This Letter presents a search for a heavy neutral particle decaying into an opposite-sign different-flavor dilepton pair, e±μ±, e±τ±, or μ±τ± using 20.3 fb-1 of pp collision data at s=8 TeV collected by the ATLAS detector at the LHC. The numbers of observed candidate events are compatible with the standard model expectations. Limits are set on the cross section of new phenomena in two scenarios: the production of ντ in R-parity-violating supersymmetric models and the production of a lepton-flavor-violating Z′ vector boson.